Alkyne-substituted N-heterophenes - Hahn, Sebastian; Koser, Silke; Hodecker, Manuel; Tverskoy, Olena; Rominger, Frank; Dreuw, Andreas; Bunz, Uwe H. F. (Chemistry - a European journal, 2017)
The synthesis and characterization of novel S-shaped N-heterophenes is reported. The targets contain a central anthracene connected to two heterophenanthrene units. N-Heterophenes are synthesized by reacting Boldt's 1,2,6,7-anthracenetetraone with different dialkynylated ortho-diaminobenzenes. The condensation yields range from 63 to 75 %; all of the N-heterophenes are stable and isolable.